PERSONAL MASTERY AND PEAK PERFORMANCE MINDSET FOR LEADERSA SUCCESS SYSTEM TO CREATE DESIRED PROFESSIONAL/BUSINESS RESULTS - Ali Athar Ahmed, Mohammed (Digital Repository of Theses - SSBM Geneva, 2023)
According to Smagulova (2022), entrepreneurship requires an entrepreneur to be a person of superior ability who pursues their goals despite obstacles, opposition, setbacks, and failure. They must persist in the face of adversity, confront unknown challenges, risk, and learn from failures, have confidence in their capacity to deal with the world, and take practical, rational steps in pursuing goals. The successful entrepreneur tends to be a visionary, competent, independent, actionoriented, passionate, confident, and virtuous person who uses reason to focus their enthusiasm on reality to attain goals. The observation of Assel Smagulova also applies to seasoned business leaders who tend to lose their edge after a few failures or setbacks. This study explores Personal Mastery and Peak Performance Mindset for people in leadership positions to enable them to tap into their inner and external resources and achieve business success.